Potential Probiotic Strains From Milk and Water Kefir Grains in Singapore—Use for Defense Against Enteric Bacterial Pathogens - Tan, Li Ling; Tan, Chuan Hao; Ng, Noele Kai Jing; Tan, Yoke Hun; Conway, Patricia Lynne; Loo, Say Chye Joachim (Frontiers in Microbiology, 2022)
Kefir grains consist of complex symbiotic mixtures of bacteria and yeasts, and are reported to impart numerous health-boosting properties to milk and water kefir beverages. The objective of this work was to investigate the microbial communities in kefir grains, and explore the possibility of deriving useful probiotic strains from them. A total of 158 microbial strains, representing 6 fungal and 17 bacterial species, were isolated from milk and water kefir grains collected from a Singapore-based homebrewer . Based on 16S rRNA sequencing, isolated genera included Lactobacillus, Liquorilactobacillus, Lacticaseibacillus, Lentilactobacillus, Leuconostoc, Lactococcus, Acetobacter, Gluconobacter, Oenococcus, Clostridium, Zymomonas, Saccharomyces, Kluyveromyces, Pichia, Lachancea, Candida and Brettanomyces. To characterize these isolates, a funnel approach, involving numerous phenotypic and genomic screening assays, was applied to identify kefir-derived microbial strains with the highest probiotic potential. Particular focus was placed on examining the pathogen inhibitory properties of kefir isolates towards enteric pathogens which pose a considerable global health burden. Enteric pathogens tested include species of Bacillus, Salmonella, Vibrio, Clostridium, Klebsiella, Escherichia and Staphylococcus. Well diffusion assays were conducted to determine the propensity of kefir isolates to inhibit growth of enteric pathogens, and a competitive adhesion/exclusion assay was used to determine the ability of kefir isolates to out-compete or exclude attachment of enteric pathogens to Caco-2 cells. Seven bacterial strains of Lentilactobacillus hilgardii, Lacticaseibacillus paracasei, Liquorilactobacillus satsumensis, Lactobacillus helveticus and Lentilactobacillus kefiri, were ultimately identified as potential probiotics, and combined to form a “kefir probiotics blend”. Desirable probiotic characteristics, including good survival in acid and bile environments, bile salt hydrolase activity, antioxidant activity, non-cytotoxicity and high adhesion to Caco-2 cells, and a lack of virulence or antimicrobial resistance genes. In addition, vitamin and γ-aminobutyric acid (GABA) synthesis genes, were identified in these kefir isolates. Overall, probiotic candidates derived in this study are well-characterized strains with a good safety profile which can serve as novel agents to combat enteric diseases. These kefir-derived probiotics also add diversity to the existing repertoire of probiotic strains, and may provide consumers with alternative product formats to attain the health benefits of kefir.